METHODS, HARDWARE AND SOFTWARE FOR RESEARCH OF BLOOD VESSELS AND TISSUES OF THE HUMAN EYE - S. A. Lisenko; V. A. Firago; A. I. Kubarko; M. M. Kugeiko (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The article provides the reader with a number of strategies to the research of blood vessels and tissues of human eye by contactless optical methods. Techniques and apparatus for measuring of geometric parameters of the blood vessels, blood flow velocity and concentrations of ocular tissues chromophores are described. The research is aimed to reveal the most effective diagnostic criteria of vascular abnormalities by means of affordable to measure indicators.